2023
DOI: 10.48550/arxiv.2303.16137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

XRBcats: Galactic High Mass X-ray Binary Catalogue

Abstract: Context. We present a new catalogue of the high-mass X-ray binaries (HMXBs) in the Galaxy improving upon the most recent such catalogue. We include new HMXBs discovered since aforementioned publication and revise the classification for several objects previously considered HMXBs or candidates. The catalogue includes both basic information such as source names, coordinates, types, and more detailed data such as distance and X-ray luminosity estimates, binary system parameters and other characteristic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…However, such low birth masses are in conflict with BHs in high-mass X-ray binaries (HMXBs), where a compact object accretes matter from the stellar winds of a young and massive (5 M e ) companion. Of the many known HMXBs (>100 in the MW alone; see the recent catalogs of Fortin et al 2023;Neumann et al 2023), three are known to host dynamically confirmed BHs: Cygnus X-1, with a BH mass of 21.2 ± 2.2 M e and an age of ∼4 Myr (Miller-Jones et al 2021); LMC X-1, with a BH mass of 10.91 ± 1.41 M e and an age of ∼5 Myr (Orosz et al 2009); and M33 X-7, with a BH mass of 11.4 M e and an age of ∼5.8 Myr (Ramachandran et al 2022). Because their accretion is fed from the winds of the companion, these BHs likely have masses close to their natal values.…”
Section: Could Horizonless Bhs Form With Subsolar Masses?mentioning
confidence: 99%
“…However, such low birth masses are in conflict with BHs in high-mass X-ray binaries (HMXBs), where a compact object accretes matter from the stellar winds of a young and massive (5 M e ) companion. Of the many known HMXBs (>100 in the MW alone; see the recent catalogs of Fortin et al 2023;Neumann et al 2023), three are known to host dynamically confirmed BHs: Cygnus X-1, with a BH mass of 21.2 ± 2.2 M e and an age of ∼4 Myr (Miller-Jones et al 2021); LMC X-1, with a BH mass of 10.91 ± 1.41 M e and an age of ∼5 Myr (Orosz et al 2009); and M33 X-7, with a BH mass of 11.4 M e and an age of ∼5.8 Myr (Ramachandran et al 2022). Because their accretion is fed from the winds of the companion, these BHs likely have masses close to their natal values.…”
Section: Could Horizonless Bhs Form With Subsolar Masses?mentioning
confidence: 99%
“…We consider the Fermi/LAT sensitivity in the ∼10−100 GeV band (after 4 years of survey) and that expected for CTAs in the ∼ 0.1 − 100 TeV band (after 50 hours of observations 3 ). To date, we know in our Galaxy ∼ 54 Be/XRBs and 32 HMXBs with OB supergiant stars (Neumann et al 2023;Fortin et al 2023;Arnason et al 2021;Liu et al 2006). For some Be/XRBs, there are indications that during X-ray outbursts, an accretion disc forms around the pulsar (e.g.…”
Section: Observability Of Hmxbs In the γ−Ray Bandmentioning
confidence: 98%
“…Note that the probability is similarly low for a neutron star LMXB to be observed within an SNR, as they have similar numbers and mass-transfer rates. On the other hand, windaccreting high-mass X-ray binaries have lifetimes of order 1 Myr, rather than 1 Gyr, so the expectation value of the number of high-mass X-ray binaries associated with SNRs, given the 169 known high-mass X-ray binaries (Neumann et al 2023), is 169 × (30,000/10 6 ) ∼ 5, consistent with the small number of known high-mass X-ray binary-SNR associations in our Galaxy (Clark & Murdin 1978;Heinz et al 2013), and in the LMC (Maitra et al 2019(Maitra et al , 2021. Xing & Li (2021) perform a more thorough population analysis, indeed predicting that a few Be X-ray binaries should be associated with SNRs.…”
Section: Evolutionary Considerationsmentioning
confidence: 99%